Preventive interventions for children of parents with depression, anxiety, or bipolar disorder: A quasi‐experimental clinical trial. (10th October 2022) - Wirehag Nordh, Emme‐Lina; Grip, Karin; Thorvaldsson, Valgeir; Priebe, Gisela; Afzelius, Maria; Axberg, Ulf
Abstract: Aim: To investigate the effectiveness of preventive interventions for 8–17‐year‐old children of patients diagnosed with depression, anxiety, or bipolar disorder. Methods: Sixty‐two families including 89 children received either the more extensive Family Talk Intervention (FTI; n = 35), the brief Let's Talk about Children (LTC; n = 16), or Interventions as Usual (IAU; n = 38) in routine care in adult psychiatry. Parent‐rated questionnaire data were collected at baseline, after 6 and 12 months. We used growth curve models to investigate the effect of intervention on child mental health problems (SDQ‐P Total Difficulties) and perceived parental control of child behaviour (PLOC‐PPC). Results: Parents in the FTI and LTC groups, versus the IAU group, reported more favourable development in terms of preventing increase in child mental health problems with standardised intervention effects of d = −0.86 and −0.88 respectively, by study end, and reported improved perceived parental control, d = 1.08 and 0.71, respectively, by study end. No significant differences in effect were found when FTI and LTC were compared. Conclusions: The results support continued use of FTI and LTC in adult psychiatry, and since LTC is a brief intervention, it might be useful as a minimum‐level preventive intervention.